Academic and Career Development: Rethinking Advising for Asian American Students. Issue 160 (20th December 2017) - Kodama, Corinne M.; Huynh, Jill
Abstract: Academic and career development for Asian American students is complicated by cultural influences, interdependence with family, and racial stereotyping. This chapter highlights research, theory, and practice to help educators rethink traditional advising approaches to more appropriately work with Asian American students as they navigate their academics and careers.